2019
DOI: 10.1371/journal.pone.0217781
|View full text |Cite
|
Sign up to set email alerts
|

Associations between GLUT expression and SUV values derived from FDG-PET in different tumors—A systematic review and meta analysis

Abstract: Purpose Fluorodeoxyglucose-Positron-emission tomography (FDG-PET), quantified by standardized uptake values (SUV), is one of the most used functional imaging modality in clinical routine. It is widely acknowledged to be strongly associated with Glucose-transporter family (GLUT)-expression in tumors, which mediates the glucose uptake into cells. The present systematic review sought to elucidate the association between GLUT 1 and 3 expression with SUV values in various tumors. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 102 publications
1
33
0
1
Order By: Relevance
“…In terms of another prognostic marker in our results, glycolysis signature, it is notable that glucose metabolism profiles can be noninvasively estimated by FDG PET. GLUT score, calculated by GLUT1 and GLUT3, was reported as the major deterministic factor for the FDG uptake in various studies (10,15,21,22), while a recent study showed a moderate correlation between FDG uptake and GLUT regarding a complex mechanism of glucose metabolism (23). Furthermore, glycolysis activity is also associated with FDG uptake in vivo (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of another prognostic marker in our results, glycolysis signature, it is notable that glucose metabolism profiles can be noninvasively estimated by FDG PET. GLUT score, calculated by GLUT1 and GLUT3, was reported as the major deterministic factor for the FDG uptake in various studies (10,15,21,22), while a recent study showed a moderate correlation between FDG uptake and GLUT regarding a complex mechanism of glucose metabolism (23). Furthermore, glycolysis activity is also associated with FDG uptake in vivo (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced FDG uptake re ect the heterogeneity of glucose metabolism. The correlation between GLUT-1 and FDG uptake was found in multiple malignancies such as breast cancer [21], lung cancer [22], cervical cancer [23] pancreatic cancer [24] and colorectal cancer [12] et al However, Ran Hong's study show that the GLUT-1 expression was not associated with FDG uptake, the discrepancy between two studies may be caused by differences in FDG parameters, only one radio-parameter was included in Ran Hong's research [25]. There was few study regarded to the relationship between MACC1 and FDG uptake, the present study demonstrated a statistical correlation between MACC1 expression and TLG of CRC patients for the rst time.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of 18 F-FDG re ect the tracer uptake by tumor cells and provides objective data on tumor glucose metabolism. Recently, the correlation between radio-parameters derived from FDG-PET and tumor biomarkers has been extensively investigated, especially GLUT-1, high expression of GLUT-1 is identi ed as promote the FDG uptake in wide variety of solid tumors [12]. However, the role of MACC1 in contribute to FDG uptake needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Marom and colleagues reported that neither GLUT1 nor GLUT3 protein levels correlated with 2-FDG uptake in 73 patients with early-stage, non-small cell lung carcinoma [103]. In a recent review, Mayer and colleagues mentioned that GLUT expression and SUV derived from 2-FDG-PET were only moderately associated in various cancers [104]. These studies cast doubt that GLUTs are responsible for enhanced glucose uptake in cancerous cells, although involvement of non-canonical GLUTs such as GLUT12 could not be excluded [105].…”
Section: Evaluating Glucose Uptake In Cancer Cells Using Radiolabeledmentioning
confidence: 99%
“…In 1996, Matsuoka and colleagues published three consecutive papers about a novel d-glucose tracer [109][110][111]. By reacting NBD-chloride with 2-amino-2-deoxy- expression and SUV derived from 2-FDG-PET were only moderately associated in various cancers [104]. These studies cast doubt that GLUTs are responsible for enhanced glucose uptake in cancerous cells, although involvement of non-canonical GLUTs such as GLUT12 could not be excluded [105].…”
Section: Monitoring Glucose Uptake Into Single Cells With Fluorescencmentioning
confidence: 99%